From the conservation of genetic diversity to the promotion of quality foodstuff: can the French model of 'Appellation d'Origine Contrôlée' be exported? - Boisvert, Valérie (International Food Policy Research Institute, 2006)
Building on ongoing research, this paper aims at suggesting alternative ways to conventional IPR systems to promote local varieties and related knowledge in developing countries. Many attempts to protect genetic diversity and local knowledge through IPR are in jeopardy because of misunderstanding on the terms of the debate and misrepresentation of the claims and interests of the various stakeholders. The paper then suggests that to improve rural livelihood conditions and promote genetic diversity conservation, it would be more efficient and satisfactory for the parties involved to build on local perceptions of foodstuff production and associated knowledge. It is easier and more feasible to stress the importance of a given know-how in the processing of products from genetically diversified or highly specific resources, than to isolate indigenous or local contributions in the conservation of genetic resources. This simplifies the remuneration issue and reinforces the legitimacy of local claims. Finally the paper discusses the feasibility, expected advantages and drawbacks of an adaptation of the French system of Appellation d’Origine Contrôlée (AOC) — a type of geographical indication of origin — for developing countries..